La constellation comme pratique créatrice chez Virginia Woolf et Annie Ernaux - Suzel Meyer (Glad!)
The Years (1937), a novel by Virginia Woolf, and Les Années (2008), a non-fiction book by Annie Ernaux, are two ways of a feminine writing of history, written by and through the mind and experience of particular women. This history of the nineteenth, twentieth and twenty-first centuries is written with many allusions, quotations, cultural and historical references. This writing « in rhizomes » or rather in constellations shows the feminine et feminist culture of the authors and their partly autobiographical texts, and contributes to their feminist stance. By revealing the heritage that formed the woman, the author et the book, feminist thought informs their situated way of writing the world. The practice of quotation allows authors to be part of a cultural history, to think about the writing of herstory, and to contribute to building a feminist memory in literature. Constellations writing thus nourishes both literary practice and feminist thought.